2002
DOI: 10.1088/0266-5611/18/6/328
|View full text |Cite
|
Sign up to set email alerts
|

Robust solutions of inverse problems in electromagnetic non-destructive evaluation

Abstract: Non-destructive testing (NDT) is the application of physical measurement technology based on energy interaction with the material and its nonconformities. The material’s response is sensed by transducers and sensors which—in most cases—scan the component and document the results in inspection images. However, NDT measures a physically defined quantity or even an intrinsic property. The difference between non-destructive evaluation (NDE) and NDT is in the interpretation of the inspection data. NDE has to discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 7 publications
(17 reference statements)
0
40
0
1
Order By: Relevance
“…7, there are two peaks in each group of MBN signals, the lower peak depends on the content of cementite and the higher peak is caused by ferrite phase. 19) Though the micro-defect information is included in the MBN signals, a proper signal index is very important to correlate the defect information and the signal. Index values (feature parameter of MBN signals) such as the "Energy" of the MBN signal have been proposed.…”
Section: Testing Principle and Procedures 231 Mbn Methodsmentioning
confidence: 99%
“…7, there are two peaks in each group of MBN signals, the lower peak depends on the content of cementite and the higher peak is caused by ferrite phase. 19) Though the micro-defect information is included in the MBN signals, a proper signal index is very important to correlate the defect information and the signal. Index values (feature parameter of MBN signals) such as the "Energy" of the MBN signal have been proposed.…”
Section: Testing Principle and Procedures 231 Mbn Methodsmentioning
confidence: 99%
“…2 is a characteristic of the material and/or component being considered. A large number of parameters have been derived from a variety of research work performed [17,18], where Fraunhofer IZFP has currently identified 42 of those. Major characteristics of a magnetic hysteresis is the saturation level, the magnetic flux at H = 0 called remanence and the field strength required to achieve B = 0 called coercivity.…”
Section: Magnetics Phenomenamentioning
confidence: 99%
“…Generally in a quasi-static frequency triangular waveform magnetic excitation condition, the excitation voltage (V E ) applied across the coil around the EM yoke is linearly related to the applied magnetic field strength (H a ) measured at the centre of the air gap between the poles of an EM yoke (in open magnetic flux path circuit). But, in the presence of a different ferromagnetic material placed between the poles of the EM yoke (to achieve closed magnetic flux path circuit), both the V E and the tangential surface magnetic field (H T ) measured on the surface of the ferromagnetic material show non-linear distortion which is considered as an influence of magnetisation of the ferromagnetic sample introduced between the poles of the EM yoke [7][8][9][10][11][12][13]. Since the magnetisation process is strongly influenced by the microstructure and stresses in ferromagnetic materials, the non-linear distortion behaviour of V E and H T is expected to have some relationship and could distinguish subtle differences in the magnetisation process between different ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%